DAMPAK KEBIJAKAN FISKAL DAN MONETER DALAM PEREKONOMIAN INDONESIA - Ada Tua Pardamean (Universitas Negeri Medan, 2013)
The trade-off between achieving price stability and economic growth, especially in the short term is the impact of a decision-making dilemma for the conduct of fiscal policy or monetary policy in the Indonesian economy. The problem is what lies behind this study and aimed to determine the impact of fiscal and monetary policies on the Indonesian economy. The data used are secondary data sourced from Bank Indonesia and BPS variables namely GDP, Government Expenditure, Tax Revenue, Export, Exchange Rate, Money Supply, Interest Rates for time series from 2000 to 2012. Data analysis was performed using Two Stage Least Squares (TSLS) estimation with multiple linear regression models using Eviews 5.0 program assistance. The results of this study it can be concluded that the simultaneous equation model on IS to variable Interest Rate and a significant negative effect on GDP of Indonesia, while the Government Expenditure variable (G0), Export (X0) and Tax Revenue (Tx) and Exchange Rate (ER) effect positively and significantly to Indonesia's GDP, while the equation for the LM model of the Money Supply variables significantly and negatively related to Indonesia's GDP increased at a rate statistically a = 10% and for variable interest rate is not significantly to Indonesia's GDP.